Hydromethanolic extracts of Morus alba L. (Mulberry) young and ripe fruit induces apoptosis in lung carcinoma cells (A549) - Payal Sargara; M. Nataraj; Ramalingam B. Subramanian; Anjali B. Thakkar (Brazilian Journal of Pharmaceutical Sciences)
Abstract The study investigates the potential of Morus alba L. (mulberry) young and ripe fruit extracts against lung cancer cells. Cancer ranking as the second leading cause of global mortality, it is essential to investigate natural compounds like phytochemicals for therapeutic benefits. The research investigates presence of phytochemicals and antioxidant activity of both young (MAF-Y) and ripe (MAF-R) mulberry fruit extracts. Results revealed presence of various secondary metabolites, particularly high phenolic content and antioxidant properties in MAF-R. Both extracts demonstrated significant cytotoxicity against lung adenocarcinoma cells (A549), with IC50 18.4 ± 3.01µg/ml (MAF-R) and 29.41 ±3.6 µg/ml (MAF-Y). Moreover, the extracts effectively inhibited cell migration. Treatment of extracts elevated reactive oxygen species (ROS) production which resulted in disruption of mitochondrial membrane potential, and induced the process of apoptosis in lung carcinoma cells. This was evidenced through various assays including differential staining and DNA fragmentation analysis. These findings underscore the potential of mulberry fruit extracts as promising candidates for cancer prevention and treatment due to their antioxidant properties, cytotoxic effects, and ability to induce apoptosis in lung cancer cells.